Myocardial Mapping in Systemic Sarcoidosis: A Comparison of Two Measurement Approaches - Dabir, Darius; Luetkens, Julian; Kuetting, Daniel; Nadal, Jennifer; Schild, Hans Heinz; Thomas, Daniel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To investigate if T1 and T2 mapping is able to differentiate between diseased and healthy myocardium in patients with systemic sarcoidosis, and to compare the standard mapping measurement (measurement within the whole myocardium of the midventricular short axis slice, SAX) to a more standardized method measuring relaxation times within the midventricular septum (ConSept).Materials and Methods 24 patients with biopsy-proven extracardiac sarcoidosis and 17 healthy control subjects were prospectively enrolled in this study and underwent CMR imaging at 1.5 T including native T1 and T2 mapping. Patients were divided into patients with (LGE+) and without (LGE–) cardiac sarcoidosis. T1 and T2 relaxation times were compared between patients and controls. Furthermore, the SAX and the ConSept approach were compared regarding differentiation between healthy and diseased myocardium.Results T1 and T2 relaxation times were significantly longer in all patients compared with controls using both the SAX and the ConSept approach (p < 0.05). However, LGE+ and LGE– patients showed no significant differences in T1 and T2 relaxation times regardless of the measurement approach used (ConSept/SAX) (p > 0.05). Direct comparison of ConSept and SAX T1 mapping showed high conformity in the discrimination between healthy and diseased myocardium (Kappa = 0.844).Conclusion T1 and T2 mapping may not only enable noninvasive recognition of cardiac involvement in patients with systemic sarcoidosis but may also serve as a marker for early cardiac involvement of the disease allowing for timely treatment. ConSept T1 mapping represents an equivalent method for tissue characterization in this population compared to the SAX approach. Further studies including follow-up examinations are necessary to confirm these preliminary results.Key Points: Citation Format
Keywords: sarcoidosis; CMR; T1 mapping; T2 mapping